La aplicación de otros métodos de valoración en el régimen de precios de transferencia - Loayza Jordán, Fernando (2017)
Prior to the last reform of the transfer pricing regime, only the application of specific valuation methods was allowed, which generated several practical and constitutional problematic issues. These were partially solved with the recent inclusion of a provision that allows the application of “other methods”. This paper analyzes the issues of the previous situation, as well as the solutions presented by the reform and its corresponding limits. Finally, the authors propose several precisions that, in their opinion, should be included in the regulation of the “other methods”.